2015
DOI: 10.1017/s0007114515003505
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental epilactose prevents metabolic disorders through uncoupling protein-1 induction in the skeletal muscle of mice fed high-fat diets

Abstract: Obesity is one of the major health problems throughout the world. The present study investigated the preventive effect of epilactose -a rare non-digestible disaccharide -on obesity and metabolic disorders in mice fed high-fat (HF) diets. Feeding with HF diets increased body weight gain, fat pad weight and adipocyte size in mice (P < 0·01), and these increases were effectively prevented by the use of supplemental epilactose without influencing food intake (P < 0·01). Caecal pools of SCFA such as acetic and prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…However, our results showed that the expression of UCP1 was significantly increased by Ex-4 treatment in differentiated C2C12 cells and mouse muscle. Recently, inducible brown adipocyte progenitors have been identified in skeletal muscle (Schulz et al 2011, Murakami et al 2015. It is not clear yet whether the increase of UCP1 expression by Ex-4 treatment is due to the effect on brown adipocyte progenitors or direct effect on muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results showed that the expression of UCP1 was significantly increased by Ex-4 treatment in differentiated C2C12 cells and mouse muscle. Recently, inducible brown adipocyte progenitors have been identified in skeletal muscle (Schulz et al 2011, Murakami et al 2015. It is not clear yet whether the increase of UCP1 expression by Ex-4 treatment is due to the effect on brown adipocyte progenitors or direct effect on muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation using C2C12 muscle cells has also highlighted that propionate was effective at increasing the gene and protein expression of UCP1, which would increase the thermogenic capacity and energy expenditure in skeletal muscle cells (Murakami et al 2015).…”
Section: The Impact Of Scfas On Skeletal Muscle Energy Metabolismmentioning
confidence: 99%
“…Only a limited number of studies suggest that the depletion of gut microbiota leads to increased muscle fatty acid catabolism18. Other accumulating indirect evidence indicates that skeletal muscle development and the metabolic profile are influenced by the ingestion of probiotics/prebiotic1920. Such findings make it tempting to speculate that a relationship may exist between muscle properties and the gut microbiota.…”
mentioning
confidence: 99%